Host range and biology of Ophelimus eucalyptii (Gahan)(Hym Eulophidae) a pest of New Zealand eucalypts - Withers, T.M.; Raman, A.; Berry, J.A. (New Zealand Plant Protection, 2000)
The gall wasp Ophelimus eucalypti (Gahan) is a pest of New Zealand Eucalyptus botryoides Sm and Eucalyptus saligna Sm (section Transversaria) The host range also includes E grandis Maiden and E deanei Maiden There were no differences between female waspinduced galls arising from E botryoides or E saligna Gall mass peaks when larvae are only one third of their maximum mass Larvae grow to fill the entire gall cavity prior to gall senescence Maximum adult emergence from galls occurs in August and December Adults live for about 10 days and females produce up to 350 eggs Three species of eulophid parasitoids attack O eucalypti in New Zealand